Care Burden of Caregivers of Palliative Patients and the Influencing Factors - Tuğba BİLGEHAN; Bahar İNKAYA (Atatürk University, 2021)
Aim: Palliative patients and caregivers of a large living space of their time are affected from many aspects including physical, psychological, social, material and spiritual. This study is a researcher-cross-sectional study of caregiver care burden and factors for palliative patients. Methods: This study was conducted with 98 caregivers who provided care for at least one month to patients hospitalized in the palliative ward of Pursaklar State Hospital between November 01, 2018 and June 15, 2019. "Sociodemographic Data Form" and "Caregiver Stress Scale (BVSÖ)" were used for data collection. In evaluating the data; Percentages, means, One Way Anova, Independent Sample t Test and Mann Whitney U test were used. For statistical significance level p <0.05 was accepted. Results: It was concluded that 59.2% of the caregivers were female, 69% were married, 93.9% had difficulties while providing care, and 89.8% received support while providing care. The total score average of the Caregiver Stress Scale of the participants was 8.94 ± 2.03, and it was observed that 87.7% had a subjective care burden. Care burden and age (p = 0.032), monthly income (p = 0.020), degree of closeness to the caregiver (p = 0.001), duration of care for the patient (p = 0.009), There is a statistically significant relationship between receiving support (p = 0.018), the area of difficulty in providing care (p = 0.023), and the duration of daily care (p = 0.000). Conclusion: In this study, which examined the care burden of individuals caring for palliative patients, it was determined that the subjective care burden was high. Providing psychological and social support for primary caregivers for palliative patients according to their needs, and raising awareness on this issue among health professionals may be recommended.